Where Are You? Tracking Kid Nightmare! (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, missing children and child abduction have happenedfrequently, which has sounded the alarm to every family with children. People paymore attention to the safety and physical health of children. The most common childtrackers on the market are smart children's watches, but the products lack hiddendesigns. Through a comparative analysis of the existing literature methodology, thisstudy found that the safety and health of children have become one of the problems ofglobalization. The application will use existing GPS and GSM technology to designnew products with concealment that will be friendly to the kids, and yet convenient totheir parents. At the same time, it has a real-time tracking function and physical activityrecord to meet the needs of parents for children's safety and health monitoring. Thisstudy will expand the theoretical knowledge and inspire practical application.